Clinical Implications of Plasma Galectin-3 in Heart Failure With Preserved Ejection Fraction: A Meta-Analysis - Shi, Yujiao; Dong, Guoju; Liu, Jiangang; Shuang, Xiong; Liu, Chunqiu; Yang, Chenguang; Qing, Wang; Qiao, Wenbo (Frontiers in Cardiovascular Medicine, 2022)
Background: Heart failure with preserved ejection fraction (HFpEF) is an increasing public health concern. Currently, data regarding the clinical application value of plasma Galectin-3 (Gal-3) in HFpEF are contradictory. Therefore, we performed the following meta-analysis to appraise the clinical implications of serum Gal-3 in HFpEF, including its capacity to predict new-onset disease, long-term unfavorable endpoints, and the degree of cardiac structural abnormality and left ventricular diastolic dysfunction (LVDD). Methods: PubMed, Embase, Scopus, and Web of Science were retrieved exhaustively from their inception until November 30, 2021, to obtain studies assessing the correlation between plasma Gal-3 and the clinical features of HFpEF (new-onset HFpEF, adverse outcomes, and echocardiographic parameters related to abnormal cardiac structure and LVDD.) Results: A total of 24 papers containing 27 studies were ultimately included in the present research. The results of the meta-analysis revealed that high plasma Gal-3 levels are strongly associated with the following clinical characteristics of HFpEF: (i) the increased risk of new-onset HFpEF (HR: 1.11; 95% CI: 1.04-1.19; p=0.910, I2 =0%; P = 0.002); (ii) the high risk of adverse outcomes of HFpEF patients (all-cause death (HR: 1.55; 95% CI: 1.27-1.87; p=0.138, I2= 42%; P = 0.000) and the composite events (all-cause death and HF hospitalization (HR: 1.50; 95% CI: 1.30-1.74; p=0.001, I2= 61%; P = 0.000) or cardiovascular (CV) death and HF hospitalization (HR: 1.71; 95% CI: 1.51-1.94; p=0.036, I2= 58%; P = 0.000)); (iii) echocardiographic indices (E/e ratio (r: 0.425, 95% CI: 0.184-0.617; p=0.000, I2= 93%; P = 0.001) and DT (r: 0.502, 95% CI: 0.061-0.779; p=0.001 I2= 91%; P = 0.027)). Conclusions: Plasma Gal-3 might be employed as an additional predictor for new-onset HFpEF, the adverse prognosis in HFpEF patients (all-cause death, the composite endpoints of all-cause death and HF hospitalization or CV death and HF hospitalization), and the severity of LVDD in HFpEF populations.